Internationalisms a twentieth-century history - Sluga, Glenda 1962-; Clavin, Patricia 1964- (Cambridge University Press, 2017)
"At the turn of the twenty-first century, historical studies of internationalism...above and beyond the call to the workers of the world to unite...have become the norm in a relatively short space of time. This shift has occurred in the context of a historical vogue for 'transnationalism,' that is, capturing experiences that traversed and transcended the borders of nation-states both within and beyond the European world. The work of the diplomatic historian Akira Iriye has been central to these developments, illuminating the traces of a distinctively twentieth century history of 'cultural internationalism' that resonated through the realms of politics. Following in the footsteps of Iriye and others...including feminist and pacifist historians who had long engaged the internationalist past...a new cohort of international historians, often sensitive to cultural analyses and with expertise in imperial and transnational as well as national histories, are now accruing broad-ranging evidence of the geographies of internationalism and the political and economic reach of its various strands at critical moments in the twentieth century"...
Keywords: Geschichte 1900-2000; HISTORY / World; Geschichte; Internationale Politik; Nationalismus; Politik; Internationalism -- History -- 20th century; Internationalism -- Political aspects -- History -- 20th century; Internationalism -- Economic aspects -- History -- 20th century; Cultural relations -- History -- 20th century; Transnationalism -- History -- 20th century; Imperialism -- History -- 20th century; Nationalism -- History -- 20th century; World politics -- 20th century; International relations -- History -- 20th century; Internationalismus; Imperialismus; Internationale Kooperation; Bürgerrechtsbewegung; Globalisierung; Soziale Bewegung; Internationale Organisation; Aufsatzsammlung